The Mediating Role of Repurchase Intention in the Relationship between Satisfaction and eWOM in Online Shopping Behavior - Loeky Rono Pradopo; Andyan Pradipta Utama; Diky Firdaus (Dinasti Review, 2026)
Abstract: This study aims to analyze the role of e-satisfaction in influencing e-WOM, both directly and indirectly through e-repurchase intention, in the context of online shopping behavior. This study uses a quantitative approach with a survey design. Data were collected through a purposive sampling technique from respondents who have shopping experience on a marketplace platform and have made repeat purchases. Data analysis was conducted using PLS to test the research model. The results showed that e-satisfaction has a positive and significant effect on e-repurchase intention and e-WOM. In addition, e-repurchase intention was proven to have a positive and significant effect on e-WOM, and mediates the relationship between e-satisfaction and e-WOM. These findings indicate that customer satisfaction not only drives repurchase intention but also strengthens consumers’ tendency to spread positive things and positive recommendations online. This contribution provides an understanding of the mediation mechanism in the relationship between e-satisfaction and e-WOM, and provides practical implications for platform managers to increase customer loyalty and positive communication through managing satisfying shopping experiences.